Reactive Silica Traces Manure Spreading in Alluvial Aquifers Affected by Nitrate Contamination: A Case Study in a High Plain of Northern Italy - Edoardo Severini (Water, 2020)
In the northern sector of the Po River Plain (Italy), widespread intensive agriculture and animal farming are supported by large amounts of water from Alpine lakes and their emissaries. Flood irrigation and excess fertilization with manure affect both the hydrology and the chemical quality of surface and groundwater, resulting in diffuse nitrogen pollution. However, studies analyzing the mechanisms linking agricultural practices with vertical and horizontal nitrogen paths are scarce in this area. We investigated groundwater quality and quantity in an unconfined, coarse-grained alluvial aquifer adjacent to the Mincio River (a tributary of the Po River), where steep summer gradients of nitrate (NO3−) concentrations are reported. The effects of manure on solutes’ vertical transport during precipitation events in fertilized and in control soils were simulated under laboratory conditions. The results show high SiO2 and NO3− leaching in fertilized soils. Similarly, field data are characterized by high SiO2 and NO3− concentrations, with a comparable spatial distribution but a different temporal evolution, suggesting their common origin but different processes affecting their concentrations in the study area. Our results show that SiO2 can be used as a conservative tracer of manure spreading, as it does not undergo biogeochemical processes that significantly alter its concentrations. On the contrary, nitrate displays large short-term variations related to aquifer recharge (i.e., flood irrigation and precipitation). In fact, aquifer recharge may promote immediate solubilization and stimulate nitrification, resulting in high NO3− concentrations up to 95.9 mg/L, exceeding the Water Framework Directive (WFD) thresholds. When recharge ends, anoxic conditions likely establish in the saturated zone, favoring denitrification and resulting in a steep decrease in NO3− concentrations.